Understanding the reverse time migration backscattering: noise or signal?. (30th September 2015) - Díaz, Esteban; Sava, Paul
ABSTRACT: Reverse time migration backscattered events are produced by the cross‐correlation between waves reflected from sharp interfaces (e.g., salt bodies). These events, along with head waves and diving waves, produce the so‐called reverse time migration artefacts, which are visible as low wavenumber energy on migrated images. Commonly, these events are seen as a drawback for the reverse time migration method because they obstruct the image of the geologic structure, which is the real objective for the process. In this paper, we perform numeric and theoretical analysis to understand the reverse time migration backscattering energy in conventional and extended images. We show that the reverse time migration backscattering contains a measure of the synchronization and focusing information between the source and receiver wavefields. We show that this synchronization and focusing information is sensitive to velocity errors; this implies that a correct velocity model produces reverse time migration backscattering with maximum energy. Therefore, before filtering the reverse time migration backscattered energy, we should try to obtain a model that maximizes it.